2022
DOI: 10.1021/acsami.1c21159
|View full text |Cite
|
Sign up to set email alerts
|

Controllable Nanoparticle Aggregation through a Superhydrophobic Laser-Induced Graphene Dynamic System for Surface-Enhanced Raman Scattering Detection

Abstract: Surface-enhanced Raman scattering (SERS) is widely used for low-concentration molecular detection; however, challenges related to detection uniformity and repeatability are bottlenecks for practical application, especially as regards ultrasensitive detection. Here, through the coupling of bionics and fluid mechanics, a lotus-leaf effect and rose-petal effect (LLE–RPE)-integrated superhydrophobic chip is facilely developed using laser-induced graphene (LIG) fabricated on a polyimide film. Dense and uniform aggr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…At present, there are few reports on SERS research of LIG integrated metal nanoparticles. Our team reported an extremely simple method to prepare the LIG SERS substrate with adjustable surface pinning performance . On this basis, we developed a SERS detection platform with controllable aggregation of gold nanoparticles (AuNPs), which achieved high efficiency and ultra-low concentration detection of a target analyte.…”
Section: Introductionmentioning
confidence: 99%
“…At present, there are few reports on SERS research of LIG integrated metal nanoparticles. Our team reported an extremely simple method to prepare the LIG SERS substrate with adjustable surface pinning performance . On this basis, we developed a SERS detection platform with controllable aggregation of gold nanoparticles (AuNPs), which achieved high efficiency and ultra-low concentration detection of a target analyte.…”
Section: Introductionmentioning
confidence: 99%
“…However, current synthesis methods of graphene require either high-temperature processing or multistep chemical synthesis routes, lessening their widespread commercial potential. Laser-induced graphene (LIG), prepared by direct laser writing on some polymer materials, has the advantages of simple preparation, easy graphic design, low cost, and excellent physicochemical properties . Its potential as a potential material for SERS substrates has not yet been fully unlocked.…”
Section: Introductionmentioning
confidence: 99%
“…To further demonstrate the advantages of Ag NWs@LIG@PDMS, the SERS performances of three similar structures of silver nanowires with laser-induced graphene embedded in PDMS (Ag NWs/LIG@PDMS), silver nanowires embedded in PDMS Ag NWs/PDMS, and silver nanowire adhesive PDMS (Ag NWs@PDMS) were also compared. The results demonstrated that the LIG interlayer could promote the deposition and stabilization of Ag NWs, , and the sophisticated structural design of Ag NWs@LIG@PDMS enabled the substrate to have the combined effect of Ag electromagnetic enhancement and LIG chemical enhancement, showing highly sensitive SERS activity. Notably, the flexible and highly sensitive SERS substrate enabled detection of organic residues on noninvasive peel surfaces by in situ surface wiping.…”
Section: Introductionmentioning
confidence: 99%
“…[19] On such a substrate, dense and uniform aggregation of nanoparticles in droplets is formed through a constant contact angle evaporation mode in the dynamic enrichment process. [20] Thus, the droplets of the mixed solution evaporate and concentrate on the tiny central area of the substrate, resulting in reliable ultrasensitive detection. [19] SERS signal reproducibility is another main factor for the ultimate SERS quantitative analysis, two-dimensional (2D) and three-dimensional (3D) nanostructure periodic arrays therefore are employed as reproducible SERS substrates, which are fabricated by particles self-assembly, [21,22] photolithography technique, [23] or template method, [24] etc.…”
Section: Introductionmentioning
confidence: 99%
“…[ 19 ] On such a substrate, dense and uniform aggregation of nanoparticles in droplets is formed through a constant contact angle evaporation mode in the dynamic enrichment process. [ 20 ] Thus, the droplets of the mixed solution evaporate and concentrate on the tiny central area of the substrate, resulting in reliable ultrasensitive detection. [ 19 ]…”
Section: Introductionmentioning
confidence: 99%